Integrative analysis of Iso-Seq and RNA-seq reveals dynamic changes of alternative promoter, alternative splicing and alternative polyadenylation during Angiotensin II-induced senescence in rat primary aortic endothelial cells - Wen, Haimei; Chen, Wei; Chen, Yu; Wei, Gang; Ni, Ting (Frontiers in Genetics, 2023)
In eukaryotes, alternative promoter (AP), alternative splicing (AS), and alternative polyadenylation (APA) are three crucial regulatory mechanisms that modulate message RNA (mRNA) diversity. Although AP, AS and APA are involved in diverse biological processess, whether they have dynamic changes in Angiotensin II (Ang II) induced senescence in rat primary aortic endothelial cells (RAECs), an important cellular model for studying cardiovascular disease, remains unclear. Here we integrated both PacBio single-molecule long-read isoform sequencing (Iso-Seq) and Illumina short-read RNA sequencing (RNA-seq) to analyze the changes of AP, AS and APA in Ang II-induced senescent RAECs. Iso-Seq generated 36,278 isoforms from 10,145 gene loci and 65.81% of these isoforms are novel, which were further cross-validated by public data obtained by other techonologies such as CAGE, PolyA-Seq and 3′READS. APA contributed most to novel isoforms, followed by AS and AP. Further investigation showed that AP, AS and APA could all contribute to the regulation of isoform, but AS has more dynamic changes compared to AP and APA upon Ang II stimulation. Genes undergoing AP, AS and APA in Ang II-treated cells are enriched in various terms and pathways related to aging or senescence, suggesting that these molecular changes are involved in functional alterations during Ang II-induced senescence. Together, the present study largely improved the annotation of rat genome and revealed gene expression changes at the isoform level, extending the understanding of the complexity of gene regulation in Ang II-treated RAECs, and also provided novel clues for discovering the regulatory mechanism undelying Ang II caused vascular senescence and diseases.